2017
DOI: 10.1002/alr.21932
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression of NK2 homeobox 1 (NKX2‐1) and goblet cell hyperplasia in nasal polyps with different endotypes

Abstract: The downregulation of NKX2-1 in IL-5 NPs may be associated with tissue eosinophilia and goblet cells hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…Although it is known that Th2 inflammation induces goblet cell hyperplasia in the lung and in nasal polyps, our group did not find any change in MUC5AC expression (a specific marker for airway goblet cells) in AR nor in CRSwNP, while other studies showed opposing findings . Recently, goblet cell hyperplasia has been shown to be specifically present in IL‐5 high NP, and therefore, it might be a specific feature of severe CRSwNP with a strong Th2 profile. An increased number of basal cells have been described in CRSwNP, possibly reflecting reduced differentiation into ciliated cells.…”
Section: Epithelial Dysfunction In the Diseased Epitheliumcontrasting
confidence: 86%
See 2 more Smart Citations
“…Although it is known that Th2 inflammation induces goblet cell hyperplasia in the lung and in nasal polyps, our group did not find any change in MUC5AC expression (a specific marker for airway goblet cells) in AR nor in CRSwNP, while other studies showed opposing findings . Recently, goblet cell hyperplasia has been shown to be specifically present in IL‐5 high NP, and therefore, it might be a specific feature of severe CRSwNP with a strong Th2 profile. An increased number of basal cells have been described in CRSwNP, possibly reflecting reduced differentiation into ciliated cells.…”
Section: Epithelial Dysfunction In the Diseased Epitheliumcontrasting
confidence: 86%
“…Mucociliary function has been described to be impaired in CRSsNP and CRSwNP, partially due to epithelial de‐differentiation (via EMT) in addition to changes in cells specification (ie changes in the proportion of basal, ciliated or goblet cells) . Recently, it has been demonstrated that primary NECs derived from nasal basal cells isolated from NP show an abnormal cilia architecture with a decreased beat frequency compared with healthy controls …”
Section: Epithelial Dysfunction In the Diseased Epitheliummentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies suggest that STAT3 transcription factors can act as transcriptional repressors by interfering with other transcription factors ( de la Iglesia et al, 2008 ; Bedel et al, 2011 ). Meanwhile other studies indicated that transcription factor SPDEF was an upstream regulator for FOXA2 expression ( Yu et al, 2010 ; Du et al, 2017 ). We found no significantly different changes in the expression of SPDEF after curcumin treatment of NCI-H292 cells (data not shown), suggesting SPDEF might not be involved in curcumin-mediated FOXA2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in goblet cell accumulation has been noted in chronic allergic airway disease as well as mouse models of chronic sinonasal inflammation. 25,26 A recent study reported increased goblet cell hyperplasia in human nasal epithelial cultures treated with IL-33 in vitro. 27 Thus, the exaggerated increase of goblet cells in Nrf2 −/− mice may be in response to the elevated expression of IL-33 (Fig.…”
Section: Discussionmentioning
confidence: 99%